Printability of papers recycled from toner and inkjet-printed papers after deinking and recycling processes - AYDEMİR, CEM; TUTAK, DOĞAN (SAGE PUBLICATIONS LTD, 2018)
Background: In our contemporary world, while part of the fibers used in the paper industry is obtained from primary fibers such as wood and agricultural plants, the rest is obtained from secondary fibers from waste papers. To manufacture paper with high optical quality from fibers of recycled waste papers, these papers require deinking and bleaching of fibers at desired levels. High efficiency in removal of ink from paper mass during recycling, and hence deinkability, are especially crucial for the optical and printability quality of the ultimate manufactured paper. Methods: In the present study, deinkability and printability performance of digitally printed paper with toner or inkjet ink were compared for the postrecycling product. To that end, opaque 80 g/m(2) office paper was digitally printed under standard printing conditions with laser toner or inkjet ink; then these sheets of paper were deinked by a deinking process based on the INGEDE method 11 p. After the deinking operation, the optical properties of the obtained recycled handsheets were compared with unprinted (reference) paper. Then the recycled paper was printed on once again under the same conditions as before with inkjet and laser printers, to monitor and measure printing color change before and after recycling, and differences in color universe. Results: Recycling and printing performances of water-based inkjet and toner-based laser printed paper were obtained. The outcomes for laser-printed recycled paper were better than those for inkjet-printed recycled paper. Conclusions: Compared for luminosity Y, brightness, CIE a* and CIE b* values, paper recycled from laser-printed paper exhibited higher value than paper recycled from inkjet-printed paper.
Keywords: Deinkability; Digital printing; Flotation; Printability; Recyclability